An assessment of sexual health risk behaviors among female youth in juvenile detention. Issue 4 (2nd October 2017) - Hatcher, Schnavia Smith; King, Dione Moultrie; Evans, Sara Z.; Summers, LaTonya M.
ABSTRACT: This study investigated the association between risky sexual behavior and drug use among female youth sentenced to a regional juvenile detention center. Preincarceration behavioral health risk data were collected from a modified version of the Youth Risk Behaviors Surveillance Survey completed by respondents. Almost all of the 105 participants had been detained before their current sentence, more than half of them were sexually active before the age of 13, and 70% had smoked marijuana or drank alcohol by age 14. A regression analysis was conducted to determine if preincarceration sexual health risk behaviors were significant enough to predict continued risk behaviors related to pregnancy, disease prevention, and substance use. Findings indicate that youth detention-based prevention programs should emphasize sexual and drug-risk reduction strategies as a means to reduce risky behaviors for this population.